2019
DOI: 10.1002/jbmr.3869
|View full text |Cite
|
Sign up to set email alerts
|

A CTGF-RUNX2-RANKL Axis in Breast and Prostate Cancer Cells Promotes Tumor Progression in Bone

Abstract: Metastasis to bone is a frequent occurrence in patients with breast and prostate cancers and inevitably threatens the patient's quality of life and survival. Identification of cancer‐derived mediators of bone metastasis and osteolysis may lead to novel therapeutic strategies. In this study, we established highly bone‐metastatic PC3 prostate and MDA‐MB‐231 (MDA) breast cancer cell sublines by in vivo selection in mice. In bone‐metastatic cancer cells, the expression and secretion of connective tissue growth fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 40 publications
2
47
0
Order By: Relevance
“…More than 90% of patients with metastatic prostate cancer will develop bone metastases and result in pathological bone destruction (Coleman, 1997). Molecular mechanism mediating the crosstalks between prostate cancer cells and bone cells leading to imbalanced bone remodelling has been an emphasis of recent research (Kim et al., 2020). Bone homeostasis is maintained and regulated by osteoblastic bone formation and osteoclastic bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…More than 90% of patients with metastatic prostate cancer will develop bone metastases and result in pathological bone destruction (Coleman, 1997). Molecular mechanism mediating the crosstalks between prostate cancer cells and bone cells leading to imbalanced bone remodelling has been an emphasis of recent research (Kim et al., 2020). Bone homeostasis is maintained and regulated by osteoblastic bone formation and osteoclastic bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicates the involvement of several transcription factors, Runx-2 [ 11 ] and Bach1 [ 12 ], in breast cancer metastasis to bone. RUNX-2 can promote breast cancer bone metastasis by increasing integrin α5-mediated colonization [ 20 ] or inducing RANKL-mediated osteoclast activation [ 21 ]. Bach1 can promote bone metastasis by enhancing the expression of metalloproteinase 1 and a chemokine receptor, CXCR4 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…39 However, pathologically, CCN2 is closely related to cancer bone metastasis. 40,41 It has been reported that αVβ3 act as a major receptor for CCN2 and mediates the migration and adhesion of endothelial and hepatic stellate cells (Figure 1). Based on this theory, Bongjun Kim et al assessed the relationship between CCN2 and αVβ3 in PCa.…”
Section: Connective Tissue Growth Factor Utilizes αVβ3 As a Receptor mentioning
confidence: 99%
“…102,103 DNA sequencing found that the receptor activator of nuclear factor kB ligand (RANKL) contains a Runx2 binding site in the promoter region. 40,104 Thus, αvβ3-induced bone matrix dissolution likely depends on the delivery of Runx2 to the nucleus to promote RANKL transcription. In terms of mechanism, Aditi Gupta et al did not provide evidence that αvβ3 could directly interact with Runx2, but they determined that αvβ3 activates Samd5.…”
Section: The αVβ3/runx2/rankl Pathway Is Closely Related To Osteolytimentioning
confidence: 99%